ASSA13-03-19 Function Role on Coronary Artery Tone of IP3 by Activating IP3R and BKCa of Porcine Coronary Artery Smooth Muscle Cells. (29th April 2013) - Yan, Yang; Peng-yun, Li; Jun, Cheng; Fang, Cai; Ming, lei; Xiao-qiu, Tan; Miao-ling, Li; Zhi-fei, Liu; Xiao-rong, Zeng
Abstract : Background and Objective: The large-conductance Ca 2+ -activated K + (BKCa ) channel mediates coronary relaxation. However, endogenous factors that regulate BKCa channel activities are not well defined. The present study sought to test the hypothesis that inositol trisphosphate (IP3) is an activator of BKCa channels in coronary smooth muscle cells (SMCs) and therefore would relax the coronary tone. Methods and Results: Porcine coronary artery rings were prepared to perform the vasomotor assay. The whole-cell voltage clamp and single-channel patch clamp experiments were performed in freshly isolated coronary SMCs to test the effect of IP3 on BKCa channels and to figure out the underlying mechanisms. The results showed that blocking IP3 receptor (IP3R) with xestospongin-C (XeC) increased the tension of coronary rings. After pre-constricting with 0.1 μM PGF2α, the use of XeC (2 μM) induced a further increase of LAD tension by 26.10 ± 5.73% (n = 4) of that induced by PGF2α, and this effect of XeC could be abolished by pretreatment with IbTX, a specific blocker of BKCa . In the perforated whole-cell recordings, in which intracellular IP3 leak cannot occur, our data confirmed that IP3 had a physiological contribution to STOC generation (approximately 30% of the STOCs are XeC-sensitivive). Under traditional whole-cell recording, introduction of exogenous IP3 (0.5–50 μM) from the pipette solution into the cytoplasm increased the XeC-sensitive STOC roughly by 30% to 50% and this effect could be abolished by XeC, suggesting that exogenous IP3 stimulates the STOC via IP3R. However, it is likely that IP3 impacts the macroscopic current (MC, another component of BKCa currents) by a differential signalling pathway. Although IP3 increased the MC, this effect could be abolished neither by XeC, nor by pretreating with 1μM thapsigargin (a depletor of SR Ca2 + store), indicating an IP3R-independent way was involved. Interestingly, in the inside-out single channel recordings, application of IP3 (10–50 μM) to the cytosolic side of the membrane increased the single BKCa channel currents likely by enhancing the Ca 2+ sensitivity of BKCa channel and as a result, changed the channel kinetics. Further, we identified that these effects were IP3R-independent. Conclusions: We conclude that IP3 is an activator of BKCa channels in the porcine coronary SMCs and can relax coronary tone.